Phenytoin-associated movement disorder: A literature review - Jamir Pitton Rissardo; Ana Letícia Fornari Caprara (Tzu Chi Medical Journal)
Phenytoin (PHT) was first synthesized as a barbiturate derivative and was approved in 1953 by the Food and Drug Administration. This work aimed to review the pathophysiology, epidemiology, clinical presentation, and treatment of PHT-associated movement disorders (MDs). Studies were searched in relevant databases (ScienceDirect, Google Scholar, Excerpta Medica, Latin American and Caribbean Health Sciences Literature, Medline, and Scientific Electronic Library Online) and were selected by two reviewers irrespective of language between 1963 and 2021. Papers of PHT-induced ataxia alone or tremor were excluded. In total, 127 reports with 219 individuals who developed MDs associated with PHT were encountered. MDs found: 126 dyskinesias, 49 myoclonus, 19 dystonia, 14 parkinsonism, 6 tics, 3 stuttering, and 2 restless legs syndrome. The mean age was 35 years (standard deviation [SD]: 23.5) and the predominant sex was male (53.4%). The mean PHT dose when the MD took place was 370.4 mg (SD: 117.5). A serum PHT concentration was reported in 103 cases, ranging from 4 to 110 μg/mL (median: 27.7 μg/mL). No significant relationship was found between PHT dose and age or PHT level. The mean onset time of PHT-associated MD was 23.4 months (SD: 4.4). The mean recovery time after MD management was 3.7 weeks (SD: 1.1). Regarding management, the most common form was PHT withdrawal in 90.4%. 86.3% of the individuals recovered fully. PHT-induced MD was extensively reported in the literature. Only general terms were used in the majority of the reports. The mechanisms underlying the adverse events caused by PHT probably depend on the presence of predisposing factors.